Application of X‐ray fluorescence spectrometry in plant science: Solutions, threats, and opportunities. (18th August 2021) - Singh, Vivek K.; Sharma, Neha; Singh, Virendra K.
Abstract : X‐ray fluorescence (XRF) spectrometry is a nondestructive, rapid, simultaneous multi‐elemental imaging methodology for plant materials. Its applications are broad and cover most of the elements with varying concentration below the parts per million ( ppm ). XRF is a well‐established atomic spectrometric technique that is also being used as a field portable instrumentation. In recent decades, XRF has been considered a very versatile tool for plant nutrition diagnosis due to its fast and multi‐elemental analytical imaging response directly from a solid sample. In this review, we have mainly focused on the recent developments and advancements in XRF spectrometry to analyze plant materials. We have also included the fundamental aspects and instrumentation for XRF spectrometry for its use in plants imaging. We have also covered the use of XRF for vegetal tissues and plant leaves. Mainly, we have briefly focused on some features of sampling procedures and calibration strategies regarding the use of XRF for plant tissues. Microchemical imaging applications by XRF, μ‐XRF, μ‐SRXRF, and TXRF have been covered for a wide variety of plant tissues such as leaves, roots, stems, and seeds.